PENGARUH SHOPPING LIFESTYLE, HEDONIC SHOPPING VALUE, DAN POSITIVE EMOTION TERHADAP IMPULSE BUYING PADA KKV TRANS STUDIO MALL BALI - Gusti Ayu Komang Tri Wahyuni; I Gusti Ayu Imbayani; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Impulse buying is a consumer behavior that needs to be studied by business actors because it is one of the effective steps that can be taken to improve marketing and is a very interesting phenomenon to study considering the large number of impulsive purchases. This research aims to determine and analyze the influence of shopping lifestyle, hedonic shopping value, and positive emotion on Impulse Buying at KKV Trans Studio Mall Bali. The population of this research are consumers who have carried out shopping activities and experienced impulse buying when shopping at KKV Trans Studio Mall Bali which is located on Jl. Iman Bonjol, Pemecutan Klod, West Denpasar District, Denpasar City, Bali, with a sample size of 130. The method used to collect data in this research was observation and questionnaire methods. The data analysis technique used is multiple linear regression analysis. The results of this research are as follows: 1) Shopping lifestyle has a positive and significant effect on impulse buying at KKV Trans Studio Mall Bali. 2) Hedonic Shopping Value has a positive and significant effect on impulse buying at KKV Trans Studio Mall Bali. 3) Positive Emotion influences impulse buying at KKV Trans Studio Mall Bali.